2018
DOI: 10.3390/md16020059
|View full text |Cite
|
Sign up to set email alerts
|

Dual Roles of Ascidian Chondromodulin-1: Promoting Cell Proliferation Whilst Suppressing the Growth of Tumor Cells

Abstract: Chondromodulin-1 (ChM-1) is an extracellular matrix protein that plays crucial roles in tumor cell growth and angiogenesis in vertebrates and humans. ChM-1 is highly expressed in the invertebrate Ciona savignyi, a marine ascidian chosen as a model. The effect of the recombinant Ciona mature ChM-1 peptide (Cs-mChM-1) on cell proliferation, migration and angiogenesis was evaluated on cultured cells. The results revealed that low concentrations of Cs-mChM-1 (12.5 nM) promoted osteoblastic cell (MC3T3-E1) growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Chm-1 expression was also detected in lacuna cells and neoplastic myoepithelial cells during the pathogenesis of pleomorphic adenoma, which is indicative of its involvement in the hypo-vascularity and chondroid formation of pleomorphic adenoma [48]. At the cellular level, Chm-1 appears to be capable of exhibiting a dual role by promoting cell proliferation and suppressing the growth of tumour cells in a dose-dependent relationship [49]. Low concentrations of Chm-1 appear to promote osteoblastic-cell growth, whereas higher concentrations of Chm-1 suppressed the growth and migration of tumour cells, such as human cervical cancer (HeLa) cells and human neuroblastoma (SH-SY5Y) cells, and inhibited the proliferation and angiogenesis of human umbilical vein endothelial cells (HUVECs) [49].…”
Section: The Role Of Chm-1 In Cancer and Heart Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Chm-1 expression was also detected in lacuna cells and neoplastic myoepithelial cells during the pathogenesis of pleomorphic adenoma, which is indicative of its involvement in the hypo-vascularity and chondroid formation of pleomorphic adenoma [48]. At the cellular level, Chm-1 appears to be capable of exhibiting a dual role by promoting cell proliferation and suppressing the growth of tumour cells in a dose-dependent relationship [49]. Low concentrations of Chm-1 appear to promote osteoblastic-cell growth, whereas higher concentrations of Chm-1 suppressed the growth and migration of tumour cells, such as human cervical cancer (HeLa) cells and human neuroblastoma (SH-SY5Y) cells, and inhibited the proliferation and angiogenesis of human umbilical vein endothelial cells (HUVECs) [49].…”
Section: The Role Of Chm-1 In Cancer and Heart Diseasementioning
confidence: 99%
“…At the cellular level, Chm-1 appears to be capable of exhibiting a dual role by promoting cell proliferation and suppressing the growth of tumour cells in a dose-dependent relationship [49]. Low concentrations of Chm-1 appear to promote osteoblastic-cell growth, whereas higher concentrations of Chm-1 suppressed the growth and migration of tumour cells, such as human cervical cancer (HeLa) cells and human neuroblastoma (SH-SY5Y) cells, and inhibited the proliferation and angiogenesis of human umbilical vein endothelial cells (HUVECs) [49]. Reports suggest that the anti-angiogenic properties of Chm-1 may contribute to the inhibitory effect of tumour progression [50, 51].…”
Section: The Role Of Chm-1 In Cancer and Heart Diseasementioning
confidence: 99%
“…In human neuroblastoma (SHSY5Y) cells, human cervical cancer (HeLa) cells, and human umbilical vein endothelial cells (HUVECs), Cs-mChM-1 suppresses cell proliferation and inhibits angiogenesis of HUVECs. Further experiments revealed that Cs-mChM-1 modifies cell behavior through regulating the cell cycle and cell adhesion [58]. These results suggest that Cs-mChM-1 is a potential antioxidant and antitumor agent.…”
Section: Diazonamidesmentioning
confidence: 78%
“…ChM-1, a 25 kDa glycoprotein originally isolated from fetal bovine cartilage, could be converted to a 12 kDa mature peptide at the C-terminal RERR amino acid cleavage site and subsequently secreted to the extracellular matrix [57]. Recently, ChM-1 was identified from the invertebrate urochordate ascidian Ciona savignyi [58]. As an invertebrate animal without cartilage and vascellum, the role of the highly expressed ChM-1 indicated its novel function.…”
Section: Diazonamidesmentioning
confidence: 99%